The Influence of Peer Pressure on Career Aspirations Among In-School Adolescent in Kwara State - Hassan , Abdulhafis Adeyinka; Esere, Mary O.; Abdulkareem , Habibat Bolanle (Universitas Pendidikan Ganesha, 2024)
The significance of career decision-making among senior high school students cannot be overemphasized. Students at this level are adolescents who are moving from this stage of development into adulthood. The study investigated the influence of peer pressure on career aspirations among in-school adolescents in Kwara State, Nigeria. It has been observed that students usually imitate themselves in their way of life, especially during the transition from upper basic education to the senior secondary stage, which determines their choice of profession. A quantitative research approach was used, and a survey research design was adopted for the study. A self-designed questionnaire was used, and an internal consistency of 0.87 for the instrument was obtained. The collected data was analyzed using Pearson’s Product Moment Correlation and a t-test to test the formulated hypotheses. Two research hypotheses were raised and tested at the 0.05 level of significance. Hypothesis one (r-cal =.204, P-value< 0.05) and hypothesis two (t-value = 3.159, P-value<0.05) were rejected. The results revealed that there is a significant relationship between peer pressure and career aspirations among in-school adolescents in Kwara State. Also, gender has a significant impact on career aspirations among in-school adolescents in Kwara State. It was recommended that educational institutions in Kwara State consider implementing peer support programs aimed at fostering positive peer influence. These programs can provide a platform for students to discuss their career aspirations, share experiences, and receive guidance from their peers.